Volunteer Police: What Predicts Confidence in Training?. (August 2019) - Dobrin, Adam; Wolf, Ross; Pepper, Ian K.; Fallik, Seth W.
Volunteer police are used in both the United States and the Unite Kingdom to expand the services provided by full-time police personnel. The models of volunteer policing that have developed in the United States and the United Kingdom are based on the same concept, but differ in their level of operational preparedness and training. The utilization and confidence of these volunteer police in performing the functions of the police has been understudied. This current study builds on previous studies to develop a broader understanding of the confidence in training of part-time volunteer police officers by using a convenience sampling of three U.K. Northern Police Forces and three U.S. Florida Sheriff's Offices. Results show the impact of individual-level variables on confidence in training preparation, with time since initial training having the largest impact. Later formal professional training appears to have little to no impact on confidence. Limitations and policy implications are discussed.